FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI TUKAR DOLLAR AMERIKA SERIKAT TERHADAP RUPIAH - Salman Al Farisi; Eni Setyowati (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
This research was conducted to determine the influence of interest rates, inflation and GDP, both simultaneously and partially, on the US dollar exchange rate on the rupiah exchange rate. The sampling technique in this research was carried out by purposive sampling. The sample used in this research is the exchange rate. This exchange rate is widely used in international trade by Indonesia. Data analysis in this research is quantitative. Using Ordinary Least Square (OLS). The results of the tests carried out revealed the fact that interest rates, inflation and GDP simultaneously had an influence on the movement of the dollar exchange rate against the rupiah.